(untitled) (Al-Academy, 2025)
The study aimed to identify the visual and intellectual culture of contemporary Saudi artists, clarify the role of Saudi Vision 2030 in changing the intellectual and cultural paradigm surrounding visual arts, and the influence of contemporary Saudi artists on economic development in the Kingdom of Saudi Arabia. Three visual works by contemporary Saudi artists, Taha Al-Sabban, Ahmed Mater, and Maha Al-Malouh, were analyzed to illustrate the visual and intellectual culture of contemporary Saudi artists and their impact on economic development in the Kingdom of Saudi Arabia. A descriptive and analytical approach was applied. The study concluded that Saudi Vision 2030 plays a prominent role in changing the visual and intellectual culture of Saudi society, and that artificial intelligence can be used as a means to enhance visual and creative capabilities. It concluded that contemporary Saudi artists have advanced to the forefront of international competition and have received financial support and attention from the state. Interest in culture and the arts has clearly contributed to economic development through various unconventional components. Culture and the arts have a clear and prominent impact in solving various social problems, including economic development.